Baeckfrutones A–L, polymethylated phloroglucinol meroterpenoids from the twigs and leaves of Baeckea frutescens. Issue 46 (15th November 2018) - Qin, Xu-Jie; Zhi, Yin-E.; Yan, Huan; Zhang, Yu; Liu, Hui; Yu, Qian; Wang, Shan; Zhao, Qing; He, Li; Ma, Xiao; An, Lin-Kun; Liu, Hai-Yang
Abstract: Twelve new polymethylated phloroglucinol meroterpenoids (PPMs), baeckfrutones A–L (1 –12 ), were isolated from the twigs and leaves of Baeckea frutescens . Their structures and absolute configurations were unambiguously established by extensive spectroscopic methods (HRESIMS, NMR, and ECD) and single crystal X-ray diffraction. PPM1 is a rare PPM comprising enone-type phloroglucinol and α -phellandrene units, whereas2 –4, 6, and7, are the first hybrids of enone-type phloroglucinol and sabinene moieties with different stereochemistry. (−)-2 and11 showed remarkable cytotoxicities against DU145 and HCT116 cells with IC50 values of 1.33 and 12.89 μM, respectively.6, 7, (+)-9, and10 displayed significant anti-inflammatory activity with inhibitory rates of 74.64, 75.37, 55.13, and 75.01% at the concentration of 50 μM, respectively. Graphical abstract: